1993
DOI: 10.1002/pd.1970131016
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of trisomy 9 mosaicism: Two new cases

Abstract: We present two prenatal cases of trisomy 9 mosaicism, both of which presented intrauterine growth retardation (IUGR) and other abnormal ultrasound findings. In case A, mosaicism was found in amniotic fluid cell cultures, of which 65 per cent were trisomic cells, on average. In case B, trisomic cells were present in amniotic fluid cell cultures (12 per cent) but none were found in fetal cord blood. After autopsy, cytogenetic findings were confirmed in different tissue cultures. It is concluded that echographic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
7
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 13 publications
5
7
0
Order By: Relevance
“…Eleven of the 12 cases exhibited a mosaic karyotype on peripheral blood analysis. However, like the present case, one of the 12 cases reportedly had a normal fetal cord blood karyotype, and analyzes of the skin and lung tissues revealed a mosaic karyotype 47,XY, + 9[17]/46,XY[83] and 47,XY, + 9[14]/46,XY[86], respectively (Merino et al 1993). Moreover, one of the 11 cases had an almost normal fetal cord blood karyotype of 47,XX, + 9[1]/ 46,XX[99], whereas cytogenetic studies of cell cultures obtained at autopsy from several fetal tissues demonstrated trisomy 9 ranging from 12 to 24% (Schwartz et al 1989).…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Eleven of the 12 cases exhibited a mosaic karyotype on peripheral blood analysis. However, like the present case, one of the 12 cases reportedly had a normal fetal cord blood karyotype, and analyzes of the skin and lung tissues revealed a mosaic karyotype 47,XY, + 9[17]/46,XY[83] and 47,XY, + 9[14]/46,XY[86], respectively (Merino et al 1993). Moreover, one of the 11 cases had an almost normal fetal cord blood karyotype of 47,XX, + 9[1]/ 46,XX[99], whereas cytogenetic studies of cell cultures obtained at autopsy from several fetal tissues demonstrated trisomy 9 ranging from 12 to 24% (Schwartz et al 1989).…”
Section: Discussionsupporting
confidence: 57%
“…Eleven of the 12 cases exhibited a mosaic karyotype on peripheral blood analysis. However, like the present case, one of the 12 cases reportedly had a normal fetal cord blood karyotype, and analyzes of the skin and lung tissues revealed a mosaic karyotype 47,XY, + 9[17]/46,XY[83] and 47,XY, + 9[14]/46,XY[86], respectively (Merino et al . 1993).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Before skin biopsy can be included in the routine evaluation of amniotic fluid mosaicism, there are H Kosztolanyi et al, 1976;Neu et al, 1969;Schinzel et al, 1974;DeBray-Ritzen et al, 1974;Meisel-Stoisiek et al, 1983 9 4 [1] -H Sherer et al, 1992;Merino et al, 1993;Saura et al, 1995;Schwartz et al, 1989 12 2 (1) 2 H Cartolano et al, 1993;von Koskull et al, 1989;Aughton et al, 1996;Patel et al, 1996 15 1 H Pletcher et al, 1994;Lindor et al, 1993;Gilbertson et al, 1990;Hsu et al, 1996 17 1 1 Kingston et al, 1993;Shaffer et al, 199618 -1 Pagon et al, 1979 1 - Hsu et al, 1987 21 -7 [3] 5 Yokoyama et al, 1992;Pagon et al, 1979;Warkany et al, 1964;Ridler et al, 1965;Zellweger et al, 1966;Haberlandt, 1973;Ladda et al, 1977 22 (1) 7 H Our case; Pagon et al, 1979;Wertelecki et al, 1986;Lessick et al, 1988;Lund et al, 1990;Desilets et al, 1996X 1 -Schlesinger et al, 1990 [ ]=Low-level mosaicism present in lymphocytes (<5 per cent); high level present in fibroblast (>50 per cent). ( )=Complete in utero evaluation including amniocentesis, cordocentesis, and skin biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…Sometimes it poses a serious problem for genetic counselling, since we must distinguish between mosaicism, pseudomosaicism, CPM, and true trisomy 9 (Hsu and Perlis, 1984;Pfeiffer et al, 1984;Appelman et al, 1991;Saura et al, 1995). Prenatal detection of trisomy 9 mosaicism in amniotic fluid can be complicated by the absence of the trisomic cell line in different tissues and the subsequent lack of fetal anomalies in some cases (Hsu and Perlis, 1984;Merino et al, 1993;Pfeiffer et al, 1984). These authors suggested that the trisomic cells may be limited to fetal membranes.…”
Section: Discussionmentioning
confidence: 99%